PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN (Studi Kasus Pada LAZNAS Nurul Hayat Kediri) - Moch. Zainuddin; Addinin Nasikhah (Istithmar: Jurnal Studi Ekonomi Syariah, 2020)
The culture of organization is a system of values and belief which is shared by The member of organization. It makes differences among the organization to other organizations. The culture of organization is also a distinguishing identity between one organization and another. In addition, Culture of organization also has an important role in employee performance. From this understanding, researchers are interested in discussing the organizational culture in LAZNAS Nurul Hayat Kediri and how the role of organizational culture in employee performance at LAZNAS Nurul Hayat Kediri. Since 2014 LAZNAS Nurul Hayat Kediri has experienced an increase in company performance, which includes increasing muzakki, and other awards. This certainly cannot be separated from the organizational culture applied to LAZNAS Nurul Hayat Kediri which adheres to a strong organizational culture. The research, entitled the role of organizational culture in improving the performance of the case study employees at LAZNAS Nurul Hayat Kediri uses a qualitative approach with the aim of obtaining a clear and objective picture. This study uses several methods in the data collection process including: observation, interviews, documentation. While the type of research used is field research, which is research that focuses on the results of data collection from predetermined informants. The results of this study indicate that the organizational culture applied to LAZNAS Nurul Hayat Kediri is more concerned with how to achieve the goals of the institution and also to realize the motto of the institution. The organizational culture applied in LAZNAS Nurul Hayat is a strong organizational culture, it will have an impact on the sincerity of employees in doing their duties and developing the institution. By implementing this strong organizational culture, employee performance will increase. This increase can be seen from the increase in the number of muzakki from 2016 to 2019, as well as other awards received by LAZNAS Nurul Hayat. With the increase in muzakki and also several awards, it shows that organizational culture has an important role in improving employee performance at LAZNAS Nurul Hayat Kediri.